2015
DOI: 10.1016/j.sbspro.2015.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Features of Gender Relations in Self-regulation of Personality

Abstract: Gender is the main part of personality, it determines the psychological and social development of a subject. The study of men's and women's features isn't a singular phenomenon, but it covers up whole society. Nowadays gender psychology is actively researching the sexuality aspects of people and their psychological differences. The aim of research study: to evolve the psychological features of personal self-management in gender relations' setting. Participants: total=80 (male: 58, female: 22). Methods of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Strengthening self-regulation skills is important because they help plan goals and achieve them (Anderson et al, 2018). Berdibayeva and Nurdaulet (2015) found that gender relations have a significant impact on self-regulation. Positive gender relations have a positive effect on the process of self-regulation.…”
Section: The Content and The Concept Of Psychological Self-regulation...mentioning
confidence: 99%
See 2 more Smart Citations
“…Strengthening self-regulation skills is important because they help plan goals and achieve them (Anderson et al, 2018). Berdibayeva and Nurdaulet (2015) found that gender relations have a significant impact on self-regulation. Positive gender relations have a positive effect on the process of self-regulation.…”
Section: The Content and The Concept Of Psychological Self-regulation...mentioning
confidence: 99%
“…Thus, a large number of studies claim that self-regulation plays a role in various spheres of life, both by promoting positive mode of behavior and preventing undesirable one. However, the positive impact of high selfregulation on the quality of social functioning (Berdibayeva et al, 2015), mental health (Eisenberg et al, 2018) and the improvement of functional status (Jouhari et al, 2015) have been reported.…”
Section: The Content and The Concept Of Psychological Self-regulation...mentioning
confidence: 99%
See 1 more Smart Citation
“…Entonces no es el aprendizaje solamente autorregulado -activado, sino que es un proceso configuracional de la subjetividad humana. Esta concepción del aprendizaje integra no sólo la actividad, la regulación y la autorregulación sino otros procesos productivos de la subjetividad humana como la imaginación y los procesos intuitivos que intervienen en esta (Absatova et al, 2014;Antonio et al, 2014;Aras, 2015;Berdibayeva et al, 2015). La tendencia a la búsqueda de problemas y su solución es una de las características distintivas de la juventud como edad psicológica que aparece en la concepción de aprendizaje desarrollador que se propone en este artículo.…”
Section: Desarrollounclassified
“…Personal self-regulation is a control of different mental activities and managing in an adequate and identified way. Self-regulation is a leading process of a personal psychological and physiological state [9]. Nowadays there is still inconsistent evidence about the role of self-regulation in addiction`s development.…”
Section: Introductionmentioning
confidence: 99%